2013
DOI: 10.1002/ijc.27986
|View full text |Cite
|
Sign up to set email alerts
|

Prospective follow‐up of 2,065 young unscreened women to study human papillomavirus incidence and clearance

Abstract: Human papillomavirus (HPV) is a necessary factor in the development of cervical intraepithelial neoplasia and cervical cancer. However, HPV is also a very common sexually transmitted virus and many women clear their infection. To study HPV incidence and clearance, 2,065 women, aged 18-29 years, were followed for 12 months and were asked to provide a self-collected cervicovaginal sample and fill-out a questionnaire every 3 months. For HPV DNA detection, the SPF 10 -DEIA LiPA 25 system was used. Incidence rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
40
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 47 publications
(122 reference statements)
7
40
2
Order By: Relevance
“…The agreement between self-collected and clinician-collected samples for the detection of HPV DNA was reasonably good in this study population, that is, 85% of positive tests were observed when both samples were available, that is, 6, 12 and 18 months. The incidence rate we observed for HR-HPV infections was essentially the same as that seen in a population of Dutch women of comparable age,27 although the latter study observed a higher rate (14.3/1000 women-months, 95% CI 12.8 to 15.9) of LR-HPVs than we did in the present study (6.9 per 1000 women-months).…”
Section: Discussionsupporting
confidence: 84%
“…The agreement between self-collected and clinician-collected samples for the detection of HPV DNA was reasonably good in this study population, that is, 85% of positive tests were observed when both samples were available, that is, 6, 12 and 18 months. The incidence rate we observed for HR-HPV infections was essentially the same as that seen in a population of Dutch women of comparable age,27 although the latter study observed a higher rate (14.3/1000 women-months, 95% CI 12.8 to 15.9) of LR-HPVs than we did in the present study (6.9 per 1000 women-months).…”
Section: Discussionsupporting
confidence: 84%
“…A prospective study of 2,065 women found a 61% spontaneous resolution rate for high-risk HPV infection within a 12-month time period. 22 This is lower than the 70% clearance demonstrated in users of the copper-containing IUD in our study; however, the difference is not statistically significant (P5.17). The 42% (95% CI 25.9-58.1%) of patients who demonstrated high-risk HPV clearance in the levonorgestrel IUD group appears significantly lower than the expected spontaneous regression of 61% (95% CI 55-67%) seen in the mentioned cohort (P5.03).…”
Section: Discussioncontrasting
confidence: 76%
“…22 However, our findings should be taken cautiously, because as a result of the retrospective nature of our research, it is only hypothesis-generating, and larger prospective studies are necessary to confirm our findings.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The clearance rates observed in our study was significantly lower than reported in studies (68.3 to 80.7%) among HIV-seronegative women. 4,2225 However previous studies amongst HIV-seropositive women have reported HPV clearance rates that are comparable 16 , higher 4,8,23,26 and even lower 19 than ours. As reported in earlier studies, we too observed lower clearance rates in women having infection with carcinogenic HPV types especially the alpha-9 species, compared to the clearance rate among carcinogenic HPV types.…”
Section: Discussioncontrasting
confidence: 59%